Deus e o Diabo na terra da cerca: a educação como expressão da luta pela terra no Assentamento Santa Helena - Tafuri, Diogo Marques (Universidade Federal de São Carlos, 2019)
In this research, we discuss the struggle for land as a social practice that generates educational processes, situating it in the specific context of the farmers’ experiences living in Santa Helena settlement, located in the rural area of São Carlos, in the state of São Paulo. In order to do so, we theoretically and conceptually base the analytical axis of our knowledge production perspective from the social practices and educational processes categories, understanding that the social practices experienced daily by human beings constitute essentially as an intersubjective praxis, generating educational processes projected in time-space from problematic gnosiological situations of social reality. Specifically, we seek to understand the diversity of experiences observed in the relationships established by farmers with the land of work throughout their different life trajectories. Historically conditioned by concrete forms of appropriation and distribution in which the landownership structure is objectified in Brazil, and thus also by the mode in which labor relations manifest in each specific space-time context, within the capitalist social production and reproduction process. Through phenomenology, we developed and organized our text obeying a historical and chronological criterion of the events described by the farmers during the interviews conducted in the field. We do so in order to contemplate the integrality of their different experiences of struggle for land and the various educational elements related to them, which have been present within their existences and which, in our understanding, integrate their ways of being and acting in the present. Finally, we argue that the phenomenon of the struggle for land presents itself as a significant and common element (in both material and symbolic terms) to a certain peasant condition in our country. Condition that has historically been constituted from the educational experience lived in the Brazilian context of land concentration and overexploitation of rural and urban labor, leading to counter-processes of political resistance that culminated, among other achievements, with the constitution of rural settlements.
God and Devil on the fence land: education as expression of the struggle for land in Santa Helena settlement
Keywords: Processos educativos; Luta pela terra; Assentamentos rurais; Questão agrária; Educational processes; Struggle for land; Rural settlements; Agrarian issue; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO